The Myb‐like transcription factor phosphorus starvation response (PtPSR) controls conditional P acquisition and remodelling in marine microalgae. Issue 6 (6th November 2019) - Kumar Sharma, Amit; Mühlroth, Alice; Jouhet, Juliette; Maréchal, Eric; Alipanah, Leila; Kissen, Ralph; Brembu, Tore; Bones, Atle M.; Winge, Per
Summary: Phosphorus (P) is one of the limiting macronutrients for algal growth in marine environments. Microalgae have developed adaptation mechanisms to P limitation that involve remodelling of internal phosphate resources and accumulation of lipids. Here, we used in silico analyses to identify the P‐stress regulator PtPSR ( Phaeodactylum tricornutum phosphorus starvation response) in the diatom P. tricornutum . ptpsr mutant lines were generated using gene editing and characterised by various molecular, genetics and biochemical tools. PtPSR belongs to a clade of Myb transcription factors that are conserved in stramenopiles and distantly related to plant P‐stress regulators. PtPSR bound specifically to a conserved cis ‐regulatory element found in the regulatory region of P‐stress‐induced genes. ptpsr knockout mutants showed reduction in cell growth under P limitation. P‐stress responses were impaired in ptpsr mutants compared with wild‐type, including reduced induction of P‐stress response genes, near to complete loss of alkaline phosphatase activity and reduced phospholipid degradation. We conclude that PtPSR is a key transcription factor influencing P scavenging, phospholipid remodelling and cell growth in adaptation to P stress in diatoms.